Pengaruh Manajemen Modal Kerja terhadap Profitabilitas Perusahaan Manufaktur di Sektor Otomotif yang Terdaftar di BEI Periode 2021–2025 - Muhammad Fhadiel Riskie; Zakki Ilham Mufli; Muhamad Ar-Rafi; Gianni Gamma Rivera; Muhammad Saefudin; Dimas Herawan (AKUNTANSI 45, 2026)
This study examines the influence of working capital management on the profitability of automotive sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2025. Working capital management is proxied through Cash Turnover (CT), Receivables Turnover (RT), Inventory Turnover (IT), and Cash Conversion Cycle (CCC), while profitability is measured using Return on Assets (ROA) and Return on Equity (ROE). A quantitative approach with a causal design was employed, using panel data from audited annual financial statements of 10 purposively selected companies, yielding 50 observations. Model selection was conducted via the Chow Test and Hausman Test, leading to the adoption of the Random Effects Model (REM) estimated with EViews 13. Results indicate that Cash Turnover has a significant positive effect on ROA but not on ROE. Receivables and Inventory Turnover show consistent significant positive effects on both ROA and ROE. The Cash Conversion Cycle has a significant negative effect on both profitability measures. Simultaneously, all four variables significantly influence profitability, with coefficients of determination of 62.43% (ROA model) and 54.78% (ROE model). These findings support the Trade-Off Theory of Liquidity and Operating Cycle Theory in the post-pandemic context of Indonesia’s automotive industry.